2012
DOI: 10.1002/jccs.201200071
|View full text |Cite
|
Sign up to set email alerts
|

Structural Studies for Specific Binding Capacity of β‐Cyclodextrin with Ibuprofen

Abstract: Ibuprofen (Ibu) and b-cyclodextrin (bCD) and its derivative (hydroxypropyl-b-cyclodextrin, HPbCD) complexes spatial geometry information were studyed. Firstly, phase solubility experiment was carried out for S-(+)-ibuprofen (SIbu) and cyclodextrins complex. The apparent stability constant (Kc) for 1:1 complexes are 1065 M-1 (bCD) and 1476 M-1 (HPbCD) respectively. Secondly, 1 H NMR and two-dimensional rotating-frame overhauser effect spectroscopy (2D ROESY) were used for binding study, and confirmed that benze… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 15 publications
1
2
0
Order By: Relevance
“…A formation constant of 9558 M −1 and an inclusion enthalpy of −3326 cal·mol −1 have been obtained by this global approach, which lead to high accuracy (±129 M −1 and ±13 cal·mol −1 for K β-CD-IBU and Δ H β-CD-IBU , respectively) owing to the high amount of experimental information. The stability is in agreement with the range of affinity (7000–14000 M −1 ) found in most published studies [ 22 27 ], even if some extreme values have also been observed [ 28 29 ]. The specificities of each individual experiment are described in the following.…”
Section: Resultssupporting
confidence: 91%
“…A formation constant of 9558 M −1 and an inclusion enthalpy of −3326 cal·mol −1 have been obtained by this global approach, which lead to high accuracy (±129 M −1 and ±13 cal·mol −1 for K β-CD-IBU and Δ H β-CD-IBU , respectively) owing to the high amount of experimental information. The stability is in agreement with the range of affinity (7000–14000 M −1 ) found in most published studies [ 22 27 ], even if some extreme values have also been observed [ 28 29 ]. The specificities of each individual experiment are described in the following.…”
Section: Resultssupporting
confidence: 91%
“…The association constant of IBR/β-CD complex falls in the range of 10 3 –10 4 M −1 [47–48], while that of MB/β-CD is less than 10 3 M −1 [4950]. According to NMR studies IBR is deeply included into the cavity [51], while MB is too large to be completely shielded by complexation. The too strong association between IBR and the cavities of CMBCD-P can be a possible reason of protection instead of catalytic decomposition in this process.…”
Section: Resultsmentioning
confidence: 99%
“…The binding mode of the interactions between the guest molecules and CDs depends on the dimensions of the organic compound and CD cavity, as well as their nature, ionization state, etc. The advantage of CDs (oligomers of α-D-glucopyranose) as chiral selectors is based on their ability to form diastereomeric inclusion complexes with enantiomeric pairs due to the intrinsic chirality [10,11].…”
Section: Introductionmentioning
confidence: 99%